PROSPEK PENGEMBANGAN KEWIRAUSAHAAN OLAHAN IKAN NILA KAWASAN DANAU TOBA DI DESA SIRUKKUNGON KECAMATAN AJIBATA KABUPATEN TOBA SAMOSIR - Roy Sahputra Saragih; Kalvin Sinaga (Politeknik Bisnis Indonesia, 2019)
The research objective is community empowerment through training on tilapia fish processing to improve entrepreneurial skills and attitudes for farmer women in Sirungkungon Village. The method to be used in research is through quasi-experiments by integrating a systemic, holistic, interdidpliner and participatory (SHIP) approach. The research activity begins with determining the priority of the problem, followed by an action plan. Recana action taken is an intervention of this research by developing entrepreneurship based on processed tilapia. The independent variable is training in entrepreneurial skills. While the dependent variable is (a) Knowledge processing various fish products and (b) entrepreneurial behavior. The proposer will get data from the public and be analyzed descriptively by finding the percentage of changes made by the paired t test with a significance level of 5% to illustrate the difference in analyzing the knowledge of existing community skills and entrepreneurial behavior. So by doing this research, it will be known the changes in behavior and skills of the peasant women of Sirungkungon Village. Crackers are foods that are very popular with all levels of society.